2021
DOI: 10.1002/pen.25776
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions

Abstract: A hybrid of poly‐l‐lactic acid (PLA) and poly‐ε‐caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45° with the increase in EA concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Indeed, PCL is a widely exploited polymer in numerous fields, including wound management; several PCL wound dressing have been produced over the years, with in vitro and in vivo studies supporting the usefulness of employing this polymer for wound healing purposes (Ehterami et al, 2018;Karizmeh et al, 2022;Thomas et al, 2015;Zhou et al, 2022). Nonetheless, one of the major drawbacks of PCL lies in its hydrophobicity, thus requiring the association with hydrophilic polymers or surface modifications allowing the interaction with biological environments (Asghari et al, 2022;Jacobs et al, 2013;Patel et al, 2021). In this direction, Porrelli and coworkers synthetized PCL-based nanofibrous scaffolds modifying their surface with air-plasma treatment to confer hydrophilicity to the final structure, thus increasing membrane wettability and allowing the interaction with cells (Porrelli, Mardirossian, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PCL is a widely exploited polymer in numerous fields, including wound management; several PCL wound dressing have been produced over the years, with in vitro and in vivo studies supporting the usefulness of employing this polymer for wound healing purposes (Ehterami et al, 2018;Karizmeh et al, 2022;Thomas et al, 2015;Zhou et al, 2022). Nonetheless, one of the major drawbacks of PCL lies in its hydrophobicity, thus requiring the association with hydrophilic polymers or surface modifications allowing the interaction with biological environments (Asghari et al, 2022;Jacobs et al, 2013;Patel et al, 2021). In this direction, Porrelli and coworkers synthetized PCL-based nanofibrous scaffolds modifying their surface with air-plasma treatment to confer hydrophilicity to the final structure, thus increasing membrane wettability and allowing the interaction with cells (Porrelli, Mardirossian, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are several fabrication techniques such as melt spinning, solution spinning, and melt blowing to create nanofibers; however, the electrospinning technique is the most popular way to produce elongated, smooth, and uniform fibers with the desired nano/microscale. , Moreover, this technique is a very uncomplicated and low-priced method. ESNFs can be used in various applications such as biomedical, drug delivery systems, environmental, water treatment (affinity membranes), and electromagnetic interference (EMI) shielding. , The fibers, with their high surface area and porosity properties, can also be used in industrial applications such as food packaging, energy storage/conversion, and sensors . Additionally, ESNFs are flexible nanomaterials suitable for catalysts in air electrodes .…”
Section: Electrospun Nanofibers (Esnfs)mentioning
confidence: 99%
“…ESNFs can be used in various applications such as biomedical, 12 drug delivery systems, 13 environmental, water treatment (affinity membranes), 14 and electromagnetic interference (EMI) shielding. 15,16 The fibers, with their high surface area and porosity properties, 21 can also be used in industrial applications such as food packaging, 17 energy storage/ conversion, 18−20 and sensors.…”
Section: Electrospun Nanofibers (Esnfs)mentioning
confidence: 99%
“…Egg albumin nanofibers were successfully developed by Patel et al and investigated for tissue engineering to increase the hydrophilicity of PLA and PCL. When compared to other albumin proteins like human serum albumin and bovine serum albumin, egg albumin is more affordable 56 . Scaffold of poly lactic‐glycolic acid (PLGA)/gelatin randomly oriented nanofibers indicated that it can benefit bone regeneration 57 .…”
Section: Applications Of Electrospun Nanofibers In the Biomedical Fieldmentioning
confidence: 99%
“…albumin is more affordable. 56 Scaffold of poly lactic-glycolic acid (PLGA)/gelatin randomly oriented nanofibers indicated that it can benefit bone regeneration. 57 Carbon nanotubes have been incorporated in multi-layered cellulose acetate nanofibers for tissue engineering to increase mechanical strength, fibroblast cells spreading, and proliferation compared with CS/ALG multilayer-assembled fibrous scaffolds.…”
Section: Characterization Of Nanofibersmentioning
confidence: 99%